2023
DOI: 10.2147/opth.s396304
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Macular Changes Under Brolucizumab Treatment for Neovascular Age-Related Macular Degeneration Refractory to Previous Anti-VEGF Treatment Compared with Treatment-Naive Eyes

Abstract: To evaluate the morphological macular changes and fluid dynamics under brolucizumab treatment in eyes refractory to previous anti-vascular endothelial growth factor (anti-VEGF) treatment for neovascular age-related macular degeneration (nAMD) compared with treatment-naive eyes. Methods: Retrospective study of all eyes treated with brolucizumab for nAMD between 2020 and 2021 with a fixed injection regimen and one year follow-up. Treatment-naive eyes (TN) were compared with eyes refractory to previous treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Mehta et al [11] found intravitreal brolucizumab (IVBr) to be well tolerated and associated with improvements in macular fluids, BCVA stabilization, and/or increased intravitreal treatment interval by studying non-naïve eyes with nAMD treated with IVBr alone or in combination with aflibercept. William et al [12] compared changes occurring in naïve eyes treated with IVBr compared with non-naïve eyes, finding improved BCVA in only naïve eyes, in contrast with foveal central thickness (FCT), which was found to be reduced in both groups.…”
Section: Introductionmentioning
confidence: 99%
“…Mehta et al [11] found intravitreal brolucizumab (IVBr) to be well tolerated and associated with improvements in macular fluids, BCVA stabilization, and/or increased intravitreal treatment interval by studying non-naïve eyes with nAMD treated with IVBr alone or in combination with aflibercept. William et al [12] compared changes occurring in naïve eyes treated with IVBr compared with non-naïve eyes, finding improved BCVA in only naïve eyes, in contrast with foveal central thickness (FCT), which was found to be reduced in both groups.…”
Section: Introductionmentioning
confidence: 99%